Recent developments on psychological factors in medically unexplained symptoms and somatoform disorders - Mewes, Ricarda (Frontiers in Public Health, 2022)
Somatic symptoms which are not fully explained by a medical condition (medically unexplained symptoms) have a high relevance for the public health. They are very common both in the general population and in patients in health care, and may develop into chronic impairing conditions such as somatoform disorders. In recent years, the relevance of specific negative psychological factors for the diagnosis and the stability of somatoform disorders and for the impairment by medically unexplained symptoms gained more and more attention. This resulted—among others- in core changes in the diagnostic classification criteria of somatoform disorders. Against this background, the present “Perspective” will outline recent developments and findings in the area of medically unexplained somatic symptoms and somatoform disorders. Moreover, it will lay a special focus on evidence on specific negative psychological factors that may influence the course of unexplained somatic symptoms and disorders and the impairment caused by these symptoms.